Answer:
(1) 56 miles/hour
Step-by-step explanation:
We need to find the average rate of change from t = 2 to t = 9.
At t = 2 hours, d = 106 miles.
At t = 9 hours, d = 498 miles.
The average rate of change in function f(x) from x = a to x = b is
[f(b) - f(a)]/(b - a)
average rate of change from t = 2 to t = 9 =
(498 - 106)/(9 - 2) = 392/7 = 56
Answer: (1) 56 miles/hour
Answer:
rate=55 percent
Step-by-step explanation:
SI=PRT
p=90
r=?
t=2
si=99
R=SI÷PT
R=99÷90×2
r=99÷180=0.55
r=0.55×100
R=55%
Step-by-step explanation:
Solution:
Given:-
(X+y,y+3)=(6,2y)
Equating corresponding elements,we get,
X+y=6------(1)
y+3=2y-----(2)
solving equation (2),
y-2y=-3
-y=-3
y=3.
Now, substituting y=3 in equation (1)
X+3=6
X=6-3
X=3
Therefore,. (X,Y) = (3,3)
Answer: 35 m
Step-by-step explanation:
The problem is the same as:
a man is fix (not moving) and the goods train is travelling at the speed of 54+72 = 126 (km/h)
Distance = 126 km/h* 8 s=126000 m/(3600 s) * 8 s=35 m